PENGARUH PENERAPAN KEGIATAN PROYEK BERKEBUN TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Nurratul Aini; Zulkifli Zulkifli; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objectivies of the research are 1) To know students cognitive skills before implementing the gardening project activity at the state kindergarten of Pembina 3 Pekanbaru. 2) To know students cognitive skills after implementing the gardening project activity at the state kindergarten of Pembina 3 Pekanbaru. 3) To know whether or not there is significant effect of the gardening project activity toward the student cognitive skills. 4) To know the significant effect implementation of the gardening project activity toward students cognitive skills among the age of 5-6 years old at the state kindergarten of Pembina 3 Pekanbaru. This research is an experimental research conducted to know the effect of a variable toward another variable in controlled condition. The subject of the research was the students at the state kindergarten of Pembina 3 Pekanbaru from the age of 5-6 years old in class B2. There are 19 students in class B2. In collecting data of the research, the writer used observation and documentation. From the research finding, it was concluded that: 1) the students cognitive skill among the age of 5-6 years old the state kindergarten of Pembina 3 Pekanbaru, before implementing the activity of the gardening project activity were classified as began to develop. It means that, in classically skills are still low. The obtained 48,68%. 2) The student cognitive skills among the age of 5-6 years old at the state kindergarten of Pembina 3 Pekanbaru after implementing the activity of the gardening project activity were classified as develop, based on the writer’s expectation. It means, in classically or in generally the students cognitive skills are good. The obtained 77,50%. 3) Implementing the gardening project activity has significant effect toward the students cognitive skills among the age of 5-6 years old at the state kindergarten Pembina 3 Pekanbaru. This can be know that there is significant difference of enhacement from the students cognitive skills before and after treatment. The gardening project activity has significant affect 56,16% toward the students cognitive skills among the age of 5-6 years old at the state kindergarten of Pembina 3 Pekanbaru.Key word : The Gardening Project Activity, Cognitive Skills